PENGARUH PENGGUNAAN MEDIA ONLINE EDMODO TERHADAP KETERAMPILAN MENULIS CERPEN MAHASISWA BAHASA DAN SASTRA INDONESIA YAYASAN ABDI PENDIDIKAN PAYAKUMBUH - Sri Mures Walef (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The background of this research is that in this era of globalization, not a few students have been able to use the internet to study or play. So the development of this technology can be utilized in learning. The development of science and technology increasingly encourages efforts to renew the use of technological results in the learning process. Lecturers are required to be able to use the tools that can be provided, and it is possible that these tools are in accordance with the development and demands of the times. Lecturers can at least use laptops and projectors. Utilization of Edmodo as a learning media for Short Story Writing Skills, especially in the eyes of kulaia, writing skills are more interesting than the lecture method. By presenting material briefly, densely and clearly, it makes students not lazy to read the material. The ease of accessing material whenever and wherever makes students able to determine for themselves when the right and comfortable time to learn so that it is better to absorb lessons. This type of research is quantitative research using the experimental method. In this study two classes were used, namely the experimental class and the control class. Experimental research is an investigation that is designed in such a way that the phenomenon or event can be socialized from the influence of other influences. This is evidenced by the change in student grades, which in the control class the mean / mean is 71.25. After using Edmodo online media in the learning process in the experimental class, changes in student learning outcomes were obtained with an average value () of 80.5. Based on the results of the t test (21.31> 1.67) it was concluded that there was a significant difference between the results of short story writing skills in the experimental class using Edmodo online media and without using Edmodo online media in the control class. This can be seen from the results of the ratio of tcount to ttable (21.31> 1.67), because tcount is greater than ttable, Ha (alternative hypothesis) is accepted, meaning that there is influence of edmodo's online media use Indonesian Level Literature and Student Level Five STKIP Foundation Payakumbuh Education Assistant.